Analisis Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Studi Pada Mahasiswa Stiem Bongaya Makassar - Sigit; Halim, Ardiansyah (Insan Cita Bongaya Research Journal, 2021)
Data collection using primary data obtained from students who study at Stiem Bongaya Makassar who are then made respondents using purposive sampling technique is a sampling technique limited to certain types of people who can provide the desired information. The results of primary data collected through the distribution of the questionnaire have been tested using classical assumptions in the form of normality assumptions, multicollinearity assumptions, heteroscedasticity assumptions, autocorrelation and linearity. Methods of data analysis using descriptive statistical analysis techniques and inferential statistical analysis. The results show that first, price has a negative effect on smartphone purchasing decisions. Both product quality have a positive and significant effect on purchasing decisions. Third, price and product quality simultaneously have a positive and significant effect on the purchase decision of a study smartphone for the Makassar Bongaya Students.